Fashion Trends and Hedonic Lifestyle on Decisions Purchase of Hijab Dresses in Bima - Haryanti, Intisari; Nurdin, Herry (Institut Agama Islam Negeri Kendari, 2019)
The phenomenon occureds in Bima, one of the cities in Indonesia, today is the excessive purchase of goods with no benefit. Most of the people decide to buy thingd only to satisfy themselves. Bima people choose to purchase clothes toput them on their social media account and get recognition from others because of trends. This research is considered a new study on fashion trends that are always changing every year. The similar research is still limited. Therefore, the researchers also explain hedonic lifestyle of Bima people. This research uses a quantitative approach with 96 respondents. The contradiction coefficient results show a strong relationship between fashion trend and hedonic lifestyle and purchase decisions. Hedonist lifestyle partially effect the purchase decision, while the fashion trend has a positive and significant effect on the purchase decision